Female-Led Firms: Performance and Risk Attitudes - Pierpaolo Parrotta; Nina Smith (Institute for the Study of Labor (IZA), 2013)
This paper investigates the relationship between gender of the CEO and composition of the board of directors (female chairman and share of women in the boardroom) and firm's risk attitudes measured as variability in four firm outcome variables (investments, profits, return to equity, and sales). Using a merged employer-employee panel sample of Danish companies with more than 50 employees, we find extensive evidence of a negative association between female CEO and firm's risk attitudes. This finding might be consistent with the theoretical assumption according to which women typically present a substantially higher risk aversion profile and put more effort in monitoring firm activities than men in the financial matter domains. A number of robustness checks corroborate and better explain our main findings.
Keywords: G34; J16; L25; 330; firm performance; risk aversion; female CEO